PENYEBAB RENDAHNYA HASIL BELAJAR SISWA TINGGAL DENGAN ORANG LAIN KELAS X SMA WISUDA PONTIANAK - Ari Yusuf; Parijo Parijo; Khosmas Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractThis study aims to determine the cause of the low learning outcomes of students who live with others on the economic subjects of grade X High School Graduation Pontianak. The method used in this research is to use qualitative research approach method. Sources of data in this study were all students of Grade X High School Graduation Pontianak who lived with other people amounted to 26 students. Data collection techniques are direct observation techniques, direct communication and documentary study techniques. While the data collection tool is the interview guide, observation sheet and triangulation. Data processing techniques using qualitative analysis techniques. Results of research based on interviews and observations and then analysis. It can be concluded that the cause of the low learning outcomes of students living with other people in the economic subjects of grade X High School Graduation Pontianak is from Factors with the following aspects: (1) Mental and physical readiness, (2) Presence, ( 3) Level of intelligence, (4) Student attitude, (5) Student talent, (6) Student interest, (7) Student motivation, (8) School environment, (9) School building situation and location, (10) learning, (11) weather condition and student's learning time in school, (12) Lack of cost, (13) Lack of study time, (14) Fatigue factor. From the results of interviews with teachers and students and from the results of observation can be concluded that students who live with others cause low student learning outcomes. Keywords: Low Learning Results of Students Living With Others On Economic Subjects